Uso del Clorhidrato de Tramadol en la disminución del dolor. en la fase activa de labor de Parto. Hospital lIPSS Juanjui, Junio 1994 - Mayo 1995 - Navarro Torres, Denis (2000)
Pain during labor causes a number of changes in homeostasis and emotional state, which if not controlled can be abolished or impair maternal and fetal well-being in both the medical and emotional aspect, the present study aimed to demonstrate the analgesic efficacy of tramadol hydrochloride in labor. Two (2) groups of 60 parturients each group A (experimental group was given 100 mg of trimadol via LM. 5 cm. Dilatation and uterine contraction in full Group B (control group were studied. ) was not given anything, in both groups the level of pain perceived by the mother as the visual analog scale assessed periodically monitored until the expulsive. blood pressure, heart rate and the occurrence of undesirable effects were found in mother and fetus. it was found that tramadol hydrochloride administered at a dose of 100 mg by LM. significantly decreases pain during childbirth is not objectified inhibition of active phenomena of labor, indeed tramadol hydrochloride proved suitable alternative for pain management in labor and delivery analgesia. No significantly altered vital signs of the mother, or adversely affects the minute APGAR shortens the active phase of labor. In conclusion recommended for use in the active phase of labor and administered during a uterine contraction.